2020
DOI: 10.1073/pnas.2006905117
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus causes maternal and fetal pathology via innate and adaptive vascular inflammation in mice

Abstract: Influenza A virus (IAV) infection during pregnancy causes severe maternal and perinatal complications, despite a lack of vertical transmission of IAV across the placenta. Here, we demonstrate a significant alteration in the maternal vascular landscape that underpins the maternal and downstream fetal pathology to IAV infection in mice. In IAV infection of nonpregnant mice, the local lung inflammatory response was contained to the lungs and was self-resolving, whereas in pregnant mice, virus dissemination to maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 40 publications
9
67
0
Order By: Relevance
“…The clinically relevant moderate dose of X31 we selected is approximately 10 times lower than comparable studies [44], yet our IAV infection model still blunted maternal weight gain without impacting litter size. Others have shown that maternal IAV infection can slow placental and fetal growth, but does not increase fetal resorption 32,45,51 , in agreement with what we report here. While we did not record placental and fetal weights, it is likely that a similar growth retardation is present in our model considering the substantial body weight reduction in pregnant dams after correcting for litter size.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The clinically relevant moderate dose of X31 we selected is approximately 10 times lower than comparable studies [44], yet our IAV infection model still blunted maternal weight gain without impacting litter size. Others have shown that maternal IAV infection can slow placental and fetal growth, but does not increase fetal resorption 32,45,51 , in agreement with what we report here. While we did not record placental and fetal weights, it is likely that a similar growth retardation is present in our model considering the substantial body weight reduction in pregnant dams after correcting for litter size.…”
Section: Discussionsupporting
confidence: 93%
“…Although viral transmission to placental tissue during murine IAV infection is rare 3,4,45,51 , we observed mild-to-moderate placental pathology within all IAV litters, similar to a previous report 4 . Infiltration of neutrophils, but not mononuclear cells, was especially apparent and is common to both bacterial-induced intrauterine inflammation 53,54 and preeclampsia 55 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Animal models show that influenza infection during pregnancy alters the placenta in multiple ways. After maternal influenza, overall placental growth is reduced ( 21 ), as well as reduced labyrinth zone thickness, suggesting that disrupted vascular development of the placenta occurs and then likely reduces nutrient and oxygen exchange ( 22 ). Maternal influenza also alters the expression of a significant number of placental genes, mainly implicating inflammatory, immune, and hypoxia pathways but also overlapping with risk genes for neuropsychiatric disorders ( 23 ).…”
Section: Maternal Inflammationmentioning
confidence: 99%